Chronic pain in the musculoskeletal system among judo athletes - Boguszewski, D.; Buda, M.; Adamczyk, J. G.; Boguszewska, K.; Obszynska-Litwiniec, A.; Bialoszewski, D. (Journal of Combat Sports and Martial Arts, 2014)
Competitive sports entail not only physical effort but often bodily injuries and chronic pain. The aim of this paper was to characterize the types of pain experienced by judo athletes. Material and methods. The survey covered 75 judo athletes. 33 of them declared that they suffer from chronic pain. The pain was evaluated with the use of the Laitinen pain questionnaire (where pain is characterized according to four categories: intensity, frequency, administration of drugs and limitation of activity). The relation between the data was determined with the use of the Pearson correlation coefficient and the differences were determined using t-distribution test for independent groups adopting p=0,05 as the minimum level of significance. Results. The general pain index was 4.33. No significant differences between the results of different subgroups of athletes were observed. The index of intensity according to the Laitinen scale was the highest (1.73) and the pain intensity index was only slightly lower (1.55). The results in the limitation of activity (0.79) and administration of drugs (0.27) categories were significantly lower (p<0.001). Conclusions. 1. Chronic pain of the musculoskeletal system was observed in the majority of athletes regardless of their age, skills and the time they have practiced judo. 2. The athletes usually felt the pain in their knees and lower back - the parts of the locomotor system which are under the greatest strain during judo trainings and fights.